Flow pattern, condensation and boiling inside and outside smooth and enhanced surfaces of propane (R290). State of the art review. (August 2021) - Mauro, A.W.; Napoli, G.; Pelella, F.; Viscito, L.
Highlights: Collection of global two-phase heat transfer coefficients and fluid flow data of propane in heat exchangers. Evaluation of boiling and condensation performance of propane and goodness of correlations in complex geometries. Collection of two-phase local data for pure propane and critical analysis on the effect of operating conditions. Abstract: A comprehensive review of two-phase flow characteristics, boiling heat transfer and condensation outside and inside tubes of propane (R290) is presented in this paper. The first section focuses on the global heat transfer performances in heat exchangers, with a collection of 11 works dealing with boiling and condensation of propane in fin and tubes, shell and tubes, plate heat exchangers and complex geometries. The second section reviews local analyses on fluid flow (8 works) and heat transfer characteristics of propane during flow boiling (23 works), pool boiling (10 works), condensation inside (13 works) and outside (2 works) single and multi-channel geometries. The critical analysis of the collected papers has the objective to provide useful information regarding the components performance for those involved in the assembly of refrigeration plants, and also to offer a critical summary on local heat transfer and fluid flow behavior of propane, particularly useful during the processes of heat exchangers design and manufacturing.